Brecht encounters "the system". Issue 1 (2nd January 2021) - Silberman, Marc
ABSTRACT: Brecht's "encounters" with Stanislavsky span the 1935 production of The Mother in New York and the 1953 Stanislavsky Conference in East Berlin, revealing the evolution in his thinking vis-à-vis his Russian counterpart. While the first encounter introduced him to American Method Acting as the epitome of dramatic theatre against which his epic theatre was aimed, it also convinced him that he needed a coherent "system" like Stanislavsky's to reach a wider audience of theatre practitioners. As a result, Brecht authored during his last years of exile the Short Organon for the Theatre . If Stanislavsky's name does not appear in it, concepts central to the epic theatre respond to Brecht's understanding of what he referred to as Aristotelian, culinary, or Naturalist theatre identified with his rival. A similar project, Buying Brass (also known as The Messingkauf Dialogues ), occupied Brecht in the years between 1939 and the early 1950's. The fragmentary texts and conversations were the closest he came to presenting a "system, " here conceived as a theory to be performed on stage as dialogues and including references to techniques employed by Stanislavsky. This essay explores key theoretical issues in the evolution of Brecht's understanding of Stanislavsky's approach to the training of actors. The closest he came to experimenting with Stanislavskian "methods" was in his 1953 production of Erwin Strittmatter's Katzgraben at the Berliner Ensemble. The documentation of rehearsals and discussions shows how Brecht used this as an opportunity to explore the affinities between the mature approaches of these two directors.